Bioactive Compounds and Biological Properties of Thunbergia laurifolia Leaf Extract and Its Potential Use as Functional Drink - Marasri Junsi (Prince of Songkla University, 2020)
Thesis (Ph.D., Food Science and Technology)--Prince of Songkla University, 2018